New Naphthoquinone Terpenoids from Marine Actinobacterium, Streptomyces sp CNQ-509 - Park, Jin-Soo; Kwon, Hak Cheol (MDPI, 2018)
A member of the marine streptomycete clade MAR4, Streptomyces sp. CNQ-509, has genetic potential for the biosynthesis of hybrid isoprenoids and produces several meroterpenoids such as naphterpin, nitropyrrolin and marinophenazine. Our research on the strain CNQ-509 led to the isolation of two new naphterpin derivatives (1 and 2) comprised of naphthoquinone and geranyl moieties along with the known terpenoid, debromomarinone. The two-dimensional structure of these compounds was determined through spectral data analysis using data from NMR, MS and UV spectroscopy. Furthermore, the full structures of 1 and 2 including absolute configurations were unequivocally established by a combination of NMR experiments and chemical modifications.
Keywords: HETEROLOGOUS EXPRESSION; GENE-CLUSTER; PRENYLATION; NAPHTHABLIN; METABOLITE; BACTERIUM; COMPOUND